Description of Microbiological Air Quality in Operating Room and Health Complaint - Wawan Supra Wismana (JURNAL KESEHATAN LINGKUNGAN, 2016)
Abstract: The hospital is a place with a fairly high degree of contamination. Operating room requires sterile conditions. The objective of this study was to describe microbiological air quality, employee characteristics, and health complaint. This was an observational study with cross sectional approach. Primary data was collected by interviewing, observing, and measuring indoor air quality of operating room. The number of responden taken was 20 employees. Data collected were analyzed descriptively with cross tabulation. The sources of air pollutants come from the anesthesia medicines and disinfectants felt by employees (15.0%). The numbers of colony forming units on the air had exceeded the recommended standards, while the temperature were still within the recommended standards. The complaints experienced by employees were dry skin and itchy skin. The most of employees characteristics were women (55.0%), age â‰¥ 35 years (55.0%), duration employment > 5 years (70.0%), working hours 7-8 hours (95.0%). The tendency of employees experience dry skin in the operating room 4 and itchy skin in the operating room 1. It is suggested to use long sleeves surgical gown, to make space between the corridor outside, to measure air exchange and maintain positive pressure, to examine health monitoring periodically, and to conduct further research to identify the microorganisms.Keywords: microbiological air quality, health complaint